Efficacy of oxamniquine, praziquantel and a combination of both drugs in schistosomiasis mansoni in Brazil - K. Zwingenberger; J. A. Nogueira Queiroz; U. Poggensee; J. E. Alencar; J. Valdegunas; F. Esmeralda; H. Feldmeier (Revista do Instituto de Medicina Tropical de São Paulo, 1987)
A randomized clinical trial was carried out to compare the efficacy of a low-dosage combination of oxamniquine (7.5 mg/kg) plus praziquantel (20 mg/kg) against either agent, oxamniquine (15 mg/kg) or praziquantel (40 mg/kg) alone, in the treatment of schistosomiasis mansoni in the Brazilian north-east. The drugs were randomly administered per os to 91 patients. Six and twelve months after treatment 89% of those admitted to the trial were reexamined by Kato-Katz method (ten slides) and MIF technique (one gram of stool) The achieved cure rates, as defined by absence of S. mansoni eggs in the faeces of individual patients at all points during the parasitological follow-up, were 81.8%, 81.2% and 67.6% for praziquantel, oxamniquine and the combination respectively. The reduction of eggs excretion in non cured patients six months after therapy ranged from 93.8-96.8% with praziquantel, 32.5-97% with oxamniquine and 76.9-99.5% with the combination. It is concluded that, at the used dosages, the three therapeutical regimens give similar and satisfactory results in the treatment of uncomplicated S. mansoni infection in Brazil.